ANALISIS EFEKTIVITAS DAN PENYAJIAN PSAP NO. 2 PADA DINAS SOSIAL KOTA MALANG TAHUN 2020–2022 - Aria Wastra Boja; Ana Sopanah S; Endah Puspitosarie (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine the conformity of the social services budget realization report in Malang City, whether it is in accordance with PSAP No. 2 as well as knowing the effectiveness of social service budget realization in Malang city. The research method used in this research is descriptive qualitative research, which is a research method that utilizes qualitative data and is described descriptively. Malang City Social Service as the object of this research. Primary data was obtained from documents contained in the Malang City Social Service. In addition, interviews were conducted with those concerned and direct observation. The results of this study indicate that Malang City is good and in accordance with the Elements of the Budget Realization Report in PSAP No. 2, starting with providing information on the realization of LRA-income in one period along with its income items, providing information on the realized expenditure budget, providing information on the realized transfer budget, providing information on the realized surplus/deficit budget, providing information on the realized surplus/deficit budget.